dDAVP Downregulates the AQP3-Mediated Glycerol Transport via V1aR in Human Colon HCT8 Cells - Centrone, Mariangela; D’Agostino, Mariagrazia; Ranieri, Marianna; Mola, Maria Grazia; Faviana, Pinuccia; Lippolis, Piero Vincenzo; Silvestris, Domenico Alessandro; Venneri, Maria; Di Mise, Annarita; Valenti, Giovanna; Tamma, Grazia (Frontiers in Cell and Developmental Biology, 2022)
Vasopressin (AVP) plays a key function in controlling body water and salt balance through the activation of the vasopressin receptors V1aR and V2R. Abnormal secretion of AVP can cause the syndrome of inappropriate antidiuresis that leads to hyponatremia, which is an electrolyte disorder often observed in the elderly hospitalized and oncologic patients. Beyond kidneys, the colonic epithelium modulates water and salt homeostasis. The water channel AQP3, expressed in villus epithelial cells is implicated in water absorption across human colonic surface cells. Here, the action of dDAVP, a stable vasopressin analog, was evaluated on the AQP3 expression and function using human colon HCT8 cells as an experimental model. Confocal and Western Blotting analysis revealed that HCT8 cells express both V1aR and V2R. Long-term (72h) treatment with dDAVP reduced glycerol uptake and cell viability. These effects were prevented by SR49059, a synthetic antagonist of V1aR, but not by tolvaptan, a specific V2R antagonist. Of note, the SR49059 action was impaired by DFP00173, a selective inhibitor of AQP3. Interestingly, compared to the normal colonic mucosa, in the colon of patients with adenocarcinoma, the expression of V1aR was significantly decreased. These findings were confirmed by gene expression analysis with RNA-Seq data. Overall, data suggest that dDAVP, through the V1aR dependent pathway, reduces AQP3 mediated glycerol uptake, a process that is reversed in adenocarcinoma, suggesting that the AVP-dependent AQP3 pathway may represent a novel target in colon diseases associated with abnormal cell growth.